Pengaruh Modal Sosial Petani Pada Pemanenan Pertanian Padi Di Kelurahan Cempa Kecamatan Cempa - ramadani, srimahyuni; Irmayani, Irmayani; Arman, Arman (Jurnal Agribis, 2024)
Social capital is the amount of resources, actual or virtual (implied) that develop in an individual or group of individuals due to the ability to have a long-lasting network of relationships that are more or less institutionalized based on mutual knowledge and acquaintance. This type of research is qualitative research. The data sources for this research are farmers and books related to this research. Meanwhile, data collection methods include interviews, observation and documentation, data processing, and analysis techniques, namely data reduction, data presentation, and conclusion. Trust among farmers can be seen from the activities carried out, including farming and the harvesting process. Social capital positively and significantly moderates the influence of trust and social networks during farmer harvesting. The trust and networks that emerge among farmers are based on strong kinship relationships that form cooperation with fellow farmers.